Post- and pre-Vatican II Council Perspectives on Church Education - Kaha, Florens Prasetio Ade Kurniawan; Viktorahadi, R.F. Bhanu (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2024)
Education is an essential matter for every individual to support both personal and social life. This has been an unchanged reality up to the present moment. The Church truly recognizes its significant role in education. However, with various changing contexts over different eras, the Church's response to education in each era also varies. Before the Second Vatican Council, the Church faced an educational situation influenced by Gallicanism, which sought to weaken the Church's influence on the state. The impact of Gallicanism on education was the existence of a state monopoly on education, leaving behind crucial aspects of education. Pope Pius XI, through Divini Illius Magistri, sought to address such a context. After the Second Vatican Council, the Church's stance, previously closed to the modern world, began to change. The Church became more open to the modern world, influencing its perspective on education. Education, which was previously more anti-modernism and anti-liberalism, has now become more open. This shift is conveyed in the document Gravissimum Educationis, published during the Second Vatican Council. The Church's development in responding to the evolving world of education is a tangible manifestation of its presence in the world.